PENDIRIAN PERSEROAN TERBATAS OLEH SUAMI ISTERI DENGAN MODAL HARTA BERSAMA - NONOT ROESITO AGAY (Fakultas Hukum Universitas Narotama, 2022)
The Supreme Court's decision Number 69/PUU-XIII/2015, states that a marriage agreement can be made free of time by husband and wife and can be related to a marriage agreement regarding the use of joint assets, including being used for capital for the establishment of a limited liability company. There are no restrictions on the marriage agreement made by husband and wife in establishing a limited liability company, because the establishment of a limited liability company is an accumulation of capital established based on an agreement in which each party is obliged to deposit capital into a limited liability company.